Clay Play on the Creativity of 4–5-Year-Old Children at State Kindergarten - A Nur Farika Saputri; M. Yusran Rahmat; Arie Martuty (ETDC: Indonesian Journal of Research and Educational Review, 2026)
The development of creativity in early childhood is a crucial aspect in education, but often the stimulation provided is not varied enough. In Amatullah Kire State Kindergarten, the level of creativity of children aged 4–5 years still requires optimization through more interactive and exploratory learning media such as clay play. This study aims to describe the application of clay play to children aged 4–5 years, determine the picture of children's creativity before and after the intervention, and test the effect of clay play on increasing children's creativity in Amatullah Kire State Kindergarten. This study used a quantitative approach with a pre-experimental design of the One-Group Pretest-Posttest type. The study sample consisted of 10 children aged 4–5 years who were given treatment in the form of structured clay play activities. Data was collected through creativity observations and analyzed using descriptive statistics and the Wilcoxon Signed Rank Test. The results showed that the application of clay play went very well with high enthusiasm from children. Children's creativity before treatment was in the medium category ("Starting to Emerge") but increased significantly after treatment to the high category ("Always Emerging"). The Wilcoxon test confirmed a significant effect with a significant value of 0.004 (p < 0.05). It was concluded that clay play is effective in enhancing the creativity of children aged 4–5 years. This study provides a practical contribution for early childhood educators in adopting clay as an effective learning method to optimize children's creative potential. Furthermore, these results serve as a scientific reference for the development of an arts-based curriculum at the kindergarten level.